2017
DOI: 10.1002/mus.25735
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of sonographic muscle thickness measurements of the thenar and hypothenar muscles

Abstract: Introduction This study was undertaken to assess the intra-and interrater reliability of sonographic thickness measurements of the thenar and hypothenar muscles. Methods: The thickness of the thenar and hypothenar muscles of both hands of 15 volunteers (7 male, 8 female) were evaluated with a 4-13-MHZ linear probe by 2 examiners who were blinded to each other's measurements. Interrater reliability was then evaluated. To assess intrarater reliability, the first examiner also performed a second measurement after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Thenar muscles (abductor pollicis brevis, adductor pollicis brevis, flexor pollicis brevis and opponens pollicis) were evaluated with the probe placed transversely over the centre of the thenar eminence, as perpendicular as possible to the tendon of the flexor pollicis longus, at the thickest thenar muscles over the first metacarpal bone, in a supine position, with forearms in supination, elbows in full extension and dorsum of the hands in contact with the examination table, for muscle thickness [44].…”
Section: Handmentioning
confidence: 99%
“…Thenar muscles (abductor pollicis brevis, adductor pollicis brevis, flexor pollicis brevis and opponens pollicis) were evaluated with the probe placed transversely over the centre of the thenar eminence, as perpendicular as possible to the tendon of the flexor pollicis longus, at the thickest thenar muscles over the first metacarpal bone, in a supine position, with forearms in supination, elbows in full extension and dorsum of the hands in contact with the examination table, for muscle thickness [44].…”
Section: Handmentioning
confidence: 99%
“…They analyzed the TMT using 1 single measurement at the approximate “middle” of the TM. [ 12 ] However, an asymmetrical thickening or partial atrophy of the TM can occur anywhere. Therefore, measurement mistakes can frequently occur.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] The merits of MRI for evaluation of the TM in CTS has already been demonstrated and have reported that the potential of MRI for detecting small anatomic lesions of the hand. [11,19,20] Previous researches of CTS have demonstrated that TM atrophy on MRI may mean irreversible TM damage, [2,12,15] but the prior studies did not evaluate the relationship between TM parameters and clinical studies. Thus, in the current research, we investigated to determine the correlations of TM parameters on MRI with clinical criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-rater reliability was not evaluated in our study for a few reasons. First, because high intra-rater and test–retest reliability of US muscle thickness measurement have already been demonstrated in the trunk muscles [ 20 , 23 , 30 , 32 ] as well as in other body regions [ 33 , 34 , 35 , 36 ]. Secondly, during semi-controlled experiments prior to the study, a high consistency was observed for the repeated US measurements among the different examiners.…”
Section: Discussionmentioning
confidence: 99%